Backflashover rate of underbuilt 33 kV distribution overhead line under lightning condition - Mohd Nawi, Zawati (2012)
Lightning has been a major concern to the power system researchers as it may cause damage to the connected electrical equipment especially to the transmission and distribution line. One of the most event is backflashover that will cause lightning overvoltage. For that reason, one study has been carried out where values of backflashover rate (BFR) on underbuilt transmission structure with characteristic of distribution line and provide the optimum placement of line arresters on phases at the tower of a distribution line to protect the line from overvoltage events. The purpose of this project is to model a 33 kV overhead distribution line for insulation coordination studies in which the investigation only focused on an underbuilt on transmission structure where the tower is also used for distribution system where the system voltage, characteristic and insulation strength are based on distribution system. A sample of worst performance underbuilt transmission structure in Peninsular Malaysia i.e. 33 kV Pantai Remis to Trong distribution line data was obtained from Tenaga Nasional Berhad (TNB). Power System Computer Aided Design, PSCAD software was used to model underbuilt distribution line components such as footing resistances, tower, insulator gap, arrester followed by doing the backflashover simulation and analysis. Besides that, the effects of line parameters such as ground resistance, soil resistivity, tower height, number of shield wire and placement line arrester on phases at the tower in lightning performance study were also investigated. Findings from backflashover analysis of Pantai Remis – Trong line using PSCAD imply that the values of backflashover rate (BFR) and also the best place to install line arrester are influenced by the values of line parameters. Right selection of line parameters may reduce BFR and the best place for installation line arrester, thus improve the distribution line performance. Findings of this research can be useful guideline towards high voltage transmission and distribution overhead line design and planning in Malaysia.